The influence of customer experience, customer relationship on customer loyalty with service as a moderating variable - Ufi Rumefi (Enrichment : Journal of Management, 2023)
Based on observations with Mr. Nur Efendik, owner of the "UD Sumber Agung" shop, sales have declined in the last few months due to intense competition, and the interest of buyers has decreased and tends to decline. According to the results of a survey on several "UD Sumber Agung" store customers who moved to other stores, it was stated that the "UD Sumber Agung" store provided poor service because the shop assistants were not friendly to customers making customers uncomfortable in choosing and buying products, besides that customers also complained because the benefits of the product purchased were not as expected and the costs incurred, as well as the lack of a good relationship between the waiter and the customer in terms of guarantees for the goods purchased. The population in this study is the customer of the "UD Sumber Agung" shop, purposive sampling technique with a sample of 50 customers. The results of the study show that the Customer Experience variable has a significant effect on Customer Loyalty. Customer Relationship variables have a significant effect on Customer Loyalty. Customer Experience moderated by service shows no significant effect on customer loyalty. The service-moderated Customer Relationship variable shows that there is a significant influence on customer loyalty..